OPTIMAL PLACEMENT OF PHASOR MEASUREMENT UNIT (PMU) ON POWER NETWORK FOR REAL-TIME VOLTAGE MEASUREMENT - Alex Aligbe; Monday F. Ohemu; Adeleke A. Hafiz; Aiyudubie S. Uyi (International Journal of Innovations in Engineering Research and Technology, 2023)
Due to the advancement in electrical power systems, there is need for control, monitoring and protection so as to improve the efficiency, reliability and security of the power network. Phasor Measurement Units (PMU) as the ability to perform enlisted task also perform operations in real-time and dynamic monitoring scenario. The aim of this research work was to optimally site PMUs on IEEE 14- Bus and IEEE 33-Bus network using Graph Theoretic Procedure Method (GTPM) with the ability to maximally observe the whole power network. For IEEE 14-Bus network 5 PMUs were required while for IEEE 33-Bus network 14 PMUs were required for full observability of the networks. The GTPM was compared with previous method used on IEEE 14-Bus network. The PMUs measured voltage magnitude and phase angle was compared with load flow analysis using Newton Raphson method.